The socioeconomic gradient of alcohol use: an analysis of nationally representative survey data from 55 low-income and middle-income countries - Xu, Yuanwei; Geldsetzer, Pascal; Manne-Goehler, Jennifer; Theilmann, Michaela; Marcus, Maja-E.; Zhumadilov, Zhaxybay; Quesnel-Crooks, Sarah; Mwalim, Omar; Moghaddam, Sahar Saeedi; Koolaji, Sogol; Karki, Khem B.; Farzadfar, Farshad; et al. (The lancet. Global health, 2022)
Background Alcohol is a leading risk factor for over 200 conditions and an important contributor to socioeconomic health inequalities. However, little is known about the associations between individuals’ socioeconomic circumstances and alcohol consumption, especially heavy episodic drinking (HED; ≥5 drinks on one occasion) in low-income or middle-income countries. We investigated the association between individual and household level socioeconomic status, and alcohol drinking habits in these settings.